Macroeconomic Activity and Role of Zaka in Achieving Economic Stability (Aggregate Supply and Economic Variable) - Alsaad, Ahmad Mohammad; Al- Rawabdeh, Shatha Musa (Journal of Economic, Administrative and Legal Sciences, 2021)
The duty of Zaka is one of the important financial resources of the Islamic state, it is also an effective tool to eliminate poverty and reduce inequality between society members. As it guarantees a regular flow of funds every year which is spent in specified channels. The obligation of Zaka has a crucial role in economic recovery because of three main factors, which prohibit hoarding, promoting investment, and encourage spending.so that is why the duty of Zaka is accomodate with economics principles. This research aims to clarify and show the economic impact of Zaka fund development through theoretical, mathematical, and graphical analysis on macroeconomics variables which is related to Aggregate Supply. Researcher used theoretical, mathematical, graphical approaches for explanation economic variables. and used deductive approach through shows the effect of zakat on the aggregate supply. researcher concludes that the duty of Zaka is an effective economic tool, and its impact on the economy is cumulative, so it is considered one of the injection elements in the Islamic economy by preventing leakage, through prohibit hoarding, that’s why it has a positive impact on the supply of human and capital resources. The researcher recommends to work on promoting the revival of Zaka, and the Zakat should be compulsory not voluntary through laws and regulations.